Cobalt ferrite nanoparticles: a magnetically separable and reusable catalyst for Petasis-Borono-Mannich reaction - Kulkarni, Aparna M.; Pandit, Kapil S.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P. (RSC Advances, 2015)
Magnetically separable cobalt ferrite nanoparticles (CoFe2O4, NPS) have been demonstrated for the first time as an efficient catalyst in Petasis-Borono-Mannich (PBM) reaction between salicylaldehydes, sec. amines and aryl boronic acids to furnish alkylaminophenols in high yields. Relatively shorter reaction times, easy purification of the products and reusability of the catalyst for five consecutive runs without appreciable loss in it's activity are the noteworthy features of the developed protocol.